PENETAPAN KADAR TOTAL ALKALOID DAN FLAVONOID PADA BINTANGUR (CALOPHYLLUM SOULLATTRI BURM.F.) MENGGUNAKAN FTIR DAN SPEKTROFOTOMETRI UV-VIS - Mitftahul Jannah; Windi Nur Fadhilah Windi; Marzella Dea Rossardy (JURNAL ETNOFARMASI, 2025)
This research aims to determine the total levels of alkaloids and flavonoids in Bintangur plants (Calophyllum soullattri burm.f.) using the FTIR method and UV-Vis spectrophotometry. The Bintangur plant is known to have various medicinal properties, such as antioxidant and anti-inflammatory. The extraction methods used include maceration, soxhletation, and reflux. The samples used were Bintangur leaves and bark, which were obtained from Tanjung Batu, Sorong City. The results showed that alkaloid and flavonoid levels could be detected well, providing a significant indication of the potential use of this plant in medicine. FTIR analysis was used to identify functional groups, while UV-Vis spectrophotometry was used to determine alkaloid and flavonoid concentrations. It is hoped that this research can contribute to the standardization of Bintangur extract in the pharmaceutical industry, as well as increasing understanding of the benefits of local medicinal plants in Indonesia. These findings are an important step in the development of safe and effective herbal products.